Changes in Antigenic Nature of Lymphocytes Caused by Common Viruses. Issue 5894 (22nd December 1973) - Thompson, Elizabeth; Lewis, Cynthia M.; Pegrum, G. D.
Abstract : Healthy human lymphocytes were incubated in the presence of influenza A2/Singapore/57, herpes simplex type 1, or adenovirus type 2. After two days the cultures were inactivated by irradiation. Fresh lymphocytes taken from the same donor were then found to react to the virus-treated cells in short-term cultures. We suggest that this reactivity is due to a change in the surface characteristics of the lymphocytes brought about by the presence of the virus. This may account for anomalous reactions in mixed lymphocyte cultures, and a similar effect in vivo might cause accelerated graft rejection.